2018
DOI: 10.1016/j.disc.2018.04.027
|View full text |Cite
|
Sign up to set email alerts
|

An improved bound for disjoint directed cycles

Abstract: We show that every directed graph with minimum out-degree at least 18k contains at least k vertex disjoint cycles. This is an improvement over the result of Alon who showed this result for digraphs of minimum out-degree at least 64k. The main benefit of the argument is that getting better results for small values of k allows for further improvements to the constant.1 A complete digraph has no loops, and between any two vertices, contains a bidirectional edge.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Alon [1] gave a linear bound by proving that 64k suffices (Lemma 11). Recently, Bucić [6] proved a better bound 18k towards this conjecture. One may find that if we apply Bucić's new bound instead of Alon's bound to our proof of Theorem 8, then we can improve the constant in the second term of Theorem 8.…”
Section: Suppose That the Bipartition Ofmentioning
confidence: 95%
“…Alon [1] gave a linear bound by proving that 64k suffices (Lemma 11). Recently, Bucić [6] proved a better bound 18k towards this conjecture. One may find that if we apply Bucić's new bound instead of Alon's bound to our proof of Theorem 8, then we can improve the constant in the second term of Theorem 8.…”
Section: Suppose That the Bipartition Ofmentioning
confidence: 95%
“…, 1) k 64k. Recently, this bound has been improved to 24k by Bucić [5]. In view of Proposition 5.3, we believe that considering (a, 2)-feasible partitions in edgecoloured graphs could be a reasonable approach for improving Bucić's result concerning Bermond and Thomassen's conjecture in digraphs.…”
Section: Claim 9 There Exists a Vertexmentioning
confidence: 82%
“…Bermond and Thomassen [4] conjectured that f (k) = 2k − 1, Alon [1] showed that f (k) 64k and recently Bucić [5] improved this bound to 24k.…”
Section: Theorem 13 (Thomassen [14]mentioning
confidence: 99%
“…It was proved for k=2 $k=2$ by Thomassen [16] and for k=3 $k=3$ by Lichiardopol, Pór, and Sereni [13]. On the other hand, Alon [1] showed that the lower bound 64k $64k$ on the minimum outdegree suffices to give k $k$ disjoint cycles and later Bucić [6] reduced this to 18k $18k$.…”
Section: Introductionmentioning
confidence: 99%
“…proved for k = 2 by Thomassen [16] and for k = 3 by Lichiardopol, Pór, and Sereni [13]. On the other hand, Alon [1] showed that the lower bound k 64 on the minimum outdegree suffices to give k disjoint cycles and later Bucić [6] reduced this to k 18 . Recently, the conjecture was verified for tournaments by Bang-Jensen, Bessy, and Thomassé [3], here a tournament is a digraph which has exactly one arc between any two vertices.…”
mentioning
confidence: 99%